Fingerroot (Boesenbergia pandurata) Extract Inhibits Proliferation and Migration of 4T1 Metastatic Breast Cancer Cells - Nurrachma, Marsya Yonna; Maran, Gergorius Gena; Putri, Nindya Budiana; Esti, Yuni Fajar; Hermawan, Adam; Meiyanto, Edy; Jenie, Riris Istighfari (Indonesian Society for Cancer Chemoprevention, 2020)
Fingerroot (Boesenbergia pandurata) is an Indonesian herb, with anti-proliferation and anti-migratory effects against several cancer cells. This study aims to investigate the anticancer property of Fingerroot Extract (FE) in combination with doxorubicin (Dox) against 4T1, a metastatic breast cancer cell lines. FE was prepared by 96% ethanol maceration and characterized by thin-layer chromatography analysis. FE was subjected to a cytotoxicity test with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay alone or in combination with 10 nM Dox against 4T1 cells. Cytotoxic effect was then confirmed by measure reactive oxygen species (ROS) intracellular level using 2’,7’-dichloroflourescin diacetate (DCFDA)-staining flow cytometry-based assay. The anti-migratory effect was observed using scratch wound healing assay and gelatin zymography to investigate matrix metalloproteinase (MMP)-9 expression. FE showed a cytotoxic effect with an inhibitory concentration 50 (IC50) value of 25.5±3.9 μg/mL and performed an improved effect in combination with 10 nM Dox. A single treatment of FE decreased ROS intracellular level, while in combination with Dox, FE increased the ROS intracellular level. Further, at 42 h observation, FE and its combination with Dox inhibited the migration of 4T1 cells with % closure of 82.6 and 82.5, respectively, correlates with a significant decrease of MMP-9 expression. Overall, FE performs a cytotoxic activity and anti-migration activity on 4T1 breast cancer cells.Keywords: Boesenbergia pandurata, cytotoxic, ROS, anti-migration, 4T1